Legislation of the Republic of Kazakhstan Regarding Criminal Infractions and the Law Enforcement Practice - NURKHAN, Aibar S. (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
Studying of issues regarding criminal infractions – whether intended or imprudent – plays quite a significant role. Fundamental changes taking part in world economy and politics, globalization processes, as well as internal dynamics of country development, undoubtedly, have impact on national legal framework, including criminal law. Therefore, the main goal of the present paper is the analysis of legislation of the Republic of Kazakhstan regarding criminal infractions and the law enforcement practice. To reach this goal authors have used methods of comparison, analysis and data systematization. As a result it has been found that in Kazakhstan there are at average 4,3 registered criminal infractions per a convict. The term of criminal infraction has appeared in the Criminal Code in 2014 to cover offences of small gravity and administrative violations that cannot be referred to the sphere of state administration. Authors have revealed the punishment in the present day Kazakhstan is not a main form of criminal responsibility realization. In the majority of cases linked to criminal infractions the persons committed them are relieved from criminal responsibility at the stage of prejudicial inquiry.